Oral Microbiology in Periodontitis - Bhonchal Bhardwaj, Sonia (IntechOpen, 2018)
This book will serve as a brief yet exhaustive guide to the role of oral microbes in health and disease. It will be useful to dental and medical students and to microbiologists.